Drill bit selection and optimization in exploration well 6507/6-4a in the Nordland ridge area - Boryczko, Piotr (University of Stavanger, Norway, 2012)
Master's thesis in Petroleum engineering The primary objective of this thesis is to analyze and optimize drilling bits which were used to drill of an exploration offshore well in Norwegian Continental Shelf (NCS). The first part ot the thesis work reviews the available drill bits and designs, including the one used in the project. I will also briefly present well 6507/6-4A and its objects in order to improve understanding the operational aspects of the project. The second part deals with drill bit optimization simulation for the well 6507/6-4A in the Nordland Ridge Area. The simulation was built based on the geological and well construction, operational real data obtained from the well. In the well 6507/6-4A, two target section were simulated using DROPS Drilling Simulator, Sesam 12 ¼” and Sesam 8 ½”. The simulation criteria was based on ROP, cost reduction and drilling time. The simulations result in increase in average ROP and decrease in both costs and duration time. PGNiG Norway